PHASEOLIN LOAMS OF THE BLACK SEA SHELF OF UKRAINE (STRUCTURE, PROPERTIES, USAGE) - YEMELIANOV, V.; LAKHNIUK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
In the paper present major characteristics – granulometric and chemical compositions as well as other structure indicators – of Phaseolin muds of the Black Sea shelf of Ukraine as a perspective resource for constructure industry.